Book Review: Misi Dalam Pandangan Ekumenikal dan Evangelikal Asia 1910-1961-1991: Book Review: Mission in the Ecumenical and Evangelical View of Asia 1910-1961-1991 - Arthur Aritonang (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
The background of the research conducted by Richard Siwu stems from the events of the Western colonial period to countries in Asia and Africa. Previously, Siwu wanted to divide this era into two periods: the colonial era and the post-colonial era. The colonial era meant the expansion of western civilization into Africa and Asia. While the post-colonial era where the end of Western domination and the birth of new nations in Africa and Asia. In colonial times, most of the countries in Asia and Africa were colonies of European nations and were politically under the control of the West. Awareness of nationalism only grew when the influence of modernization brought by Western colonialism to Africa and Asia created a form of resistance to the West which eventually gave birth to new countries. At that time there was an assumption that Christianity was a Western religion because it came along with the expansion of the West into Asia and Africa. However, the awareness of nationalism at that time encouraged the churches in Asia in particular to break away from the domination of the Western churches and also indigenize the churches in Asia with a local style. Does the end of colonialism end the mission of the church? The answer is no because from the beginning Christianity was a missionary religion read Matthew 28:19. So, this research will analyze Protestant views in Asia regarding mission from 1910 to 1991. This research shows that after the colonial era they were polarized in two main streams: ecumenical and evangelical.